Mapping the most heavily reclaimed shorelines of the Yangtze River delta urban agglomerations - Lu, Ting; Lin, Cong; Wang, Ya Ping; Wu, Hao; Zhou, Mengxiao; Chen, Yu; Shen, Yu (Frontiers in Earth Science, 2022)
Objectively understanding the characteristics and evolution of coastal geomorphology, and predicting the growth potential of intertidal flats are the prerequisites for the effective conservation and development of shoreline resources. However, the vulnerability of shorelines in the long term and large space scale needs to be assessed since human intervention in recent decades has intensified the double oppression of river delta system transformation and land reclamation. The Yangtze River Delta Urban Agglomerations (YRDUA) is a highly developed global economy, therefore, the YRDUA with the most intense reclamation, and their dynamic shoreline changes before and after the sharply decreasing sediment supply were detected based on 4596 remote sensing images and corresponding hydrodynamic data. We found that the sediment replenishment from the radial sand ridges on the middle Jiangsu Coast made the shoreline expansion rate reach 4–5 times that of other Jiangsu coasts. Specifically, a close correlation between the shoreline accretion rate and the amount of sediment supply was found on the eastern Chongming Wetland. Generally, there were still sufficient sediments on the Yangtze River Estuary and Hangzhou Bay interface to support the shoreline expansion despite the upstream sediment reduction. The longshore sediment transport from the delta-front erosion and the land reclamation including vegetation ecological responses were the main factors promoting the shoreline advance. Human interventions, dominated mainly by reclamation, formed positive feedback with local hydrodynamic processes and promoted continuous shoreline accretion. This study focused on the external and internal drivers and their interactions of long-term shoreline evolution with very intensive human activities, which can provide the decision-making reference for the regional coastal zone management and conservation.